PENGARUH PROFITABILITAS, LIKUIDITAS, TANGIBILITY ASSET, NON-DEBT TAX SHIELD, DAN PERTUMBUHAN PENJUALAN TERHADAP STRUKTUR MODAL PADA PERUSAHAAN MAKANAN DAN MINUMAN YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2013-2015 - Laela Lanjarsih; Inung Wijayanti (Aliansi : Jurnal Manajemen dan Bisnis, 2018)
This study aims to to analyze the influence of profitability, liquidity, tangibility asset, non debt tax shield, and sales growth to structure capital in the food and beverage company enrolled in indonesia stock exchange of 2013-2015.The sample from 12 company using a technique purposive sampling of the total number of 14 the food and beverage company in indonesia stock exchange 2013-2015. Data processing using data method regression panel and model’s estimation used is random effect with a significant degree 5 percent. The results of the study concluded that in partial variable profitability by return on assets (roa) have no influence to structure capital, liquidity significant negative to capital structure, tangibility asset has no influence to structure capital, variable non debt tax shield (ndts) has not been affecting the capital structure, and variable sales growth significant negative to capital structure.